Facilitators and barriers to the implementation of DIP payment methodology reform in a public hospital in Guangzhou: a qualitative study based on the implementation of the meta-framework for research (CFIR) framework - Chang, Jinghui; Chen, Siyi; Li, Anqi; Yang, Xixi; Luo, Hualian; Yilamu, Maidina; Fu, Bingqian; Xu, Nuoyan; Liu, Jing; Tian, Huishu (Frontiers in Public Health, 2025)
BackgroundThe Diagnosis-Intervention Packet (DIP), a medical insurance payment management system utilizing big data, has been piloted in 12 cities by the National Healthcare Security Administration in China starting in 2021. Guangzhou is one of the pilot cities, and it has demonstrated significant success in the DIP payment reform, with its practical experience being affirmed and promoted by the National Health Department. In this study, researchers conducted field visits to a public hospital in Guangzhou to understand the internal responses to the DIP reform and the cognitive attitudes of relevant personnel. The analysis of the positive and negative factors affecting the implementation of the reform and the proposed measures to optimize internal hospital management are expected to provide practical evidence for the implementation of DIP payment reform in other public hospitals.MethodsThis study develops an interview guide based on the Consolidated Framework for Implementation Research (CFIR) and conducts one-on-one semi-structured interviews offline with personnel from a Grade A tertiary public hospital in Guangzhou. Employing rapid qualitative analysis techniques and utilizing NVivo 14.0 for coding CFIR-structured texts related to implementation, the study integrates five dimensions: innovation, inner and outer context, individuals, and the implementation process. It identifies factors that facilitate and hinder the implementation of the Diagnosis-Intervention Packet (DIP) payment reform, thereby proposing optimized internal management strategies for public hospitals to cope with DIP payment reforms.DiscussionThis study will provide significant insights for optimizing the internal management of public hospitals in the context of DIP payment reform. It offers a reference for optimizing internal management in tertiary public hospitals in China, aiming to achieve standardized, healthy, collaborative, and high-quality development.